The current environmental legislation and characterization of the area of the nascent of Yellow Pau of the municipality Garanhuns / PE - França, Elaynne Mirele Sabino de; Gomes, Daniel Dantas Moreira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This paper conducts a study of the area covering the east of Pau yellow, which is located in the rugged southern municipality of Garanhuns - Pernambuco. To consider it as a fundamental framework dictates set by the Brazilian environmental legislation presents: New Forest Code (Law 12,651), CONAMA 303, Municipal Director Plan to assess their current application in the environmental context of this study area. We can see the need to upgrade, and application specific control of public power to the area, still punctuating the observed environmental impacts. We propose to determine in respect of the regulatory provisions that the source is an area of permanent preservation and awareness in the population that their actions are changing the quality of natural resources.